2011
DOI: 10.1161/circresaha.111.240648
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 Receptor Identifies a Pool of Human Cardiac Stem Cells With Superior Therapeutic Potential for Myocardial Regeneration

Abstract: Rationale Age and coronary artery disease may negatively affect the function of human cardiac stem cells (hCSCs) and their potential therapeutic efficacy for autologous cell transplantation in the failing heart. Objective Insulin-like growth factor 1 (IGF-1) and 2 (IGF-2), and angiotensin II (Ang II) and their receptors, IGF-1R, IGF-2R and AT1R, were characterized in c-kit-positive-hCSCs to establish whether these systems would allow us to separate hCSC classes with different growth reserve in the aging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 40 publications
2
109
0
Order By: Relevance
“…It was shown that members of IGFBP family such as IGFBP4 and IGFBP3, which are independent of binding to insulin growth factor, are involved in the processes of cardiogenesis [48][49][50]. A new subset of cardiac precursor cells that expressed insulin-like growth factor 1 receptor (IGF-1R) was found to have higher proliferation and myogenic differentiation potential compared with other CSCs subgroups [51]. Overexpression of IGFBP2, which was highly expressed in our microarray results, has been reported in common brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that members of IGFBP family such as IGFBP4 and IGFBP3, which are independent of binding to insulin growth factor, are involved in the processes of cardiogenesis [48][49][50]. A new subset of cardiac precursor cells that expressed insulin-like growth factor 1 receptor (IGF-1R) was found to have higher proliferation and myogenic differentiation potential compared with other CSCs subgroups [51]. Overexpression of IGFBP2, which was highly expressed in our microarray results, has been reported in common brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in IGF-1 display increased apoptosis of cardiomyocytes, whereas overexpression of the IGF-1 gene inhibits apoptotic cell death after MI (Li et al, 1997;Palmen et al, 2001). The c-kit þ CSCs that express IGF-1 receptor (IGF-1R) display enhanced proliferation, differentiation, and survival in response to the IGF-1/IGF-1R interaction (Linke et al, 2005;D'Amario et al, 2011). This resulted in improvement of cardiac output, ejection fraction and the left ventricular developed pressure (LVDP) after MI (Linke et al, 2005).…”
Section: Hepatocyte Growth Factor/c-metmentioning
confidence: 99%
“…Most growth factors are highly cell type specific. IGF-1 or Hepatocyte Growth Factor (HGF) have been described to exert a favorable effect on human Cardiac Stem Cells rejuvenation and mobilization in the damaged or senescent heart [20,21]. Other growth factors are known to be more pleiotropic and therefore can provide positive effects on several different cell types such as Fibroblast Growth Factor-2 or Stem Cell Factor (SCF).…”
Section: Issn: 2469-570xmentioning
confidence: 99%